Marie H. Briehl and Rosetta Hurwitz: Pioneers in North American Child Psychoanalysis. Issue 1 (1st January 2021) - Cohen, Sandra E.
ABSTRACT: This paper is a tribute and exploration of the contributions of two hidden but important figures in the history and development of North American child psychoanalysis, Marie H. Briehl and Rosetta Hurwitz. These early child psychoanalytic pioneers were the author's great-aunts. They trained as young lay analysts in Vienna with Anna Freud and other key Viennese psychoanalysts between 1924 and 1930, and were among the original group to study with Ms. Freud. The author considers various significant aspects of her great-aunt's childhoods that played a large part in the spirit of their determination to go to Vienna. She looks at their beginnings in a large socialist family, later as teachers, at their passion for the development of children, and their recognition of the limitation of pure pedagogy in reaching certain children in the classroom. The author takes the reader through Marie's and Rose's studies in Vienna and the difficulties of acceptance as lay analysts upon their return to New York City. While Rose practiced quietly in New York, this paper highlights Marie's contributions to child psychoanalysis including the development of one of the first child analytic training programs in Los Angeles, as well as her strong belief in the qualities necessary to do good child psychoanalytic work.